2018
DOI: 10.1101/494872
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

New insights from 22-kHz ultrasonic vocalizations to characterize fear responses: relationship with respiration and brain oscillatory dynamics

Abstract: Fear behavior depends on interactions between the medial prefrontal cortex (mPFC) and the basolateral amygdala (BLA), and the expression of fear involves synchronized activity in theta and gamma oscillatory activities. In addition, freezing, the most classical measure of fear response in rodents, temporally coincides with the development of sustained 4-Hz oscillations in prefrontalamygdala circuits. Interestingly, these oscillations were recently shown to depend on the animal's respiratory rhythm, supporting t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
18
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 56 publications
6
18
0
Order By: Relevance
“…However, others have found that a 4Hz oscillation develops in the mPFC during freezing behavior and that this oscillation was driven by respiration (Moberly et al, 2016;Karalis et al, 2016;Bagur and Benchenane, 2018). In line with these studies, we recently showed that respiratory frequency and delta activity frequency were highly correlated during freezing (Dupin et al, 2019). It could be hypothesized that the respiration-triggered 4Hz oscillation, when it occurs, is particularly well suited to modulate the amplitude of theta and higher frequency oscillations.…”
Section: Does Respiratory Rhythm Modulate the Temporal Patterns Obsersupporting
confidence: 80%
See 1 more Smart Citation
“…However, others have found that a 4Hz oscillation develops in the mPFC during freezing behavior and that this oscillation was driven by respiration (Moberly et al, 2016;Karalis et al, 2016;Bagur and Benchenane, 2018). In line with these studies, we recently showed that respiratory frequency and delta activity frequency were highly correlated during freezing (Dupin et al, 2019). It could be hypothesized that the respiration-triggered 4Hz oscillation, when it occurs, is particularly well suited to modulate the amplitude of theta and higher frequency oscillations.…”
Section: Does Respiratory Rhythm Modulate the Temporal Patterns Obsersupporting
confidence: 80%
“…At the behavioral level, Bad Timers showed more USV emissions during the two training sessions. USV emission is known to narrow and lower the respiratory frequency range (Frysztak and Neafsey, 1991;Hegoburu et al, 2011;Dupin et al, 2019), which might have impeded the development of clear-cut temporal patterns. In the present study, all the animals except two (out of 30) produced USVs albeit x x at different rates.…”
Section: Interval Timing and Level Of Stressmentioning
confidence: 99%
“…Individual data of LFP-respiration coupling index as a function of inhalation amplitude or duration (Fig.7) emphasized the strong and systematic coupling of this structure with respiration. PFC has been previously shown to be very well tuned to the 4 Hz respiratory frequency during animal freezing [38][39][40][41] . We show here, as we evoked in Dupin et al (2019), that the strong tuning of PFC with respiratory rhythm holds whatever the respiratory frequency.…”
Section: Discussionmentioning
confidence: 99%
“…PFC has been previously shown to be very well tuned to the 4 Hz respiratory frequency during animal freezing [38][39][40][41] . We show here, as we evoked in Dupin et al (2019), that the strong tuning of PFC with respiratory rhythm holds whatever the respiratory frequency. This suggests that PFC could function as a hub structure, able to tune its activity to that of different areas according to the respiration frequency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation